2016
DOI: 10.1016/j.amjms.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Contested Ownership of Disease and Ambulatory-Sensitive Emergency Department Visits for Type 2 Diabetes

Abstract: Background About 21 million persons have diabetes and account for 11.9% of all emergency department visits for a total cost of $14.1 billion. Non-emergent visits for ambulatory sensitive conditions that could be managed by the primary care provider make up almost one third of the ED visits. African Americans comprise about 30% of South Carolina's population but make up about 50% of the ED visits for diabetes. Methods The research design was a qualitative study using grounded theory with dimensional analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…This study is among the first to show these patients were most interested in receiving text messages that are personalized and tailored to their interests and self-care needs. Participants’ interest in handling their disease management and improving their health outcomes is consistent with the concept of ownership of diabetes as described by Shearer and colleagues [25]. We found that a majority of the medically underserved patients in this study sample already use mobile phones for personal text messaging and are highly interested in receiving health-related text messages from their doctor’s office.…”
Section: Discussionsupporting
confidence: 81%
“…This study is among the first to show these patients were most interested in receiving text messages that are personalized and tailored to their interests and self-care needs. Participants’ interest in handling their disease management and improving their health outcomes is consistent with the concept of ownership of diabetes as described by Shearer and colleagues [25]. We found that a majority of the medically underserved patients in this study sample already use mobile phones for personal text messaging and are highly interested in receiving health-related text messages from their doctor’s office.…”
Section: Discussionsupporting
confidence: 81%
“…The total unique number of patients in the nine studies was 167, ranging from 3 to 90 patients per study. All studies investigated ACSC hospitalizations except one that studied ACSC ED visits ( 23 ). Two studies used a mixed-method study design ( 24 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the patients were middle-aged and older. Four studies provided the race/ethnicity of their patients ( 22 , 23 , 27 , 28 ), while other studies discussed patients' income or poor neighborhoods ( 21 23 ), indicating that patients were socially vulnerable. Two studies did not provide a gender distribution of patients ( 23 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes, limited understanding resulted in lack of ownership of symptoms. The ownership of symptoms is complex; the experience of health care disparities may influence the decisions to act on symptoms (Shearer, Jenkins, Magwood, & Pope, ). As described by one family member: “I guess with some people they are afraid to hear what the doctor have to say.…”
Section: Resultsmentioning
confidence: 99%